Laparoscopic Marsupialization of a Giant Non-Parasitic Splenic Cyst (Npsc) in the Paediatric Age Group - Amonkar, Amol Dilip; Raghushankar, Raghushankar; Rai, Sandeep; Khan, Sattar; Ganesh, G.V. (Journal of Health and Allied Sciences NU, 2016)
Nonparasitic splenic cysts are rare clinical lesions of the spleen. The management has entailed partial or total splenectomy via an open approach. Recently, laparoscopic approaches have been developed. In this report, we describe laparoscopic marsupialization of a giant splenic cyst (diameter > 15 cm).A 15-year-old Indian child presented with a four and a half year history of mass in upper left quadrant associated with left upper quadrant pain which increased since 2 days. Physical examination revealed a large, nontender left upper quadrant mass with minimal movement on respiration. Computed tomography scan confirmed a cyst arising from the spleen, measuring 20 x 15 cm suggestive of a primary splenic cyst. Echinococcus and Entamoeba histolytica serologies were negative. Laparoscopic exploration was performed. three liters of brown fluid were aspirated and intraoperative cytology confirmed a nonparasitic cyst. The cyst wall was excised, preserving the spleen. The patient's recovery was uneventful, and he was discharged, tolerating a regular diet on postoperative day 3. At follow-up, the patient was asymptomatic and showed no evidence of recurrence. Non-parasitic splenic cysts are rare lesions. Laparoscopic marsupialization is safe and effective and should be considered the treatment of choice even for giant splenic cyst.
Keywords: laparoscopic; marsupialization; giant splenic cyst